Penggunaan Media Audio Visual Dalam Meningkatkan Hasil Belajar Pada Pelajaran Ilmu Pengetahuan Sosial Siswa Sekolah Dasar - Isna Nadifah Nur Fauziah; Selly Ade Saputri; Tin Rustini (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Learning media has an important role in improving the learning outcomes of elementary school students. Using audio-visual media can help in the social studies learning process. The purpose of this study is to find out what are the benefits of using audio-visual media in social studies learning for elementary school students. The social studies learning process is usually focused on the teacher, because of the lack of improvisation so that there is no other improvisation that causes students to feel bored and only learn the main material. So teachers need to use interesting learning media so that they can improve the quality of student learning outcomes in social studies scores. This research belongs to the type of qualitative descriptive research. With the method of collecting data using the literature study method.